ABORIGINAL EDUCATION AS CULTURAL BROKERAGE: NEW ABORIGINAL TEACHERS REFLECT ON LANGUAGE AND CULTURE IN THE CLASSROOM - Kitchen, Julian; Cherubini, Lorenzo; Trudeau, Lyn; Hodson, Janie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2010)
<!--StartFragment--> ABSTRACT. This paper reports on a Talking Circle of six beginning Aboriginal teachers who discussed their roles as teachers. Participants criticized teacher education programs for not preparing them to teach in ways that are respectful of Aboriginal languages and culture. They discussed the importance of coming to know themselves and their culture. The paper concludes with suggestions for decolonizing teacher preparation so that Aboriginal teachers are enabled as protectors of Aboriginal culture and brokers with Euro-Canadian culture. FORMER LES AUTOCHTONES COMME AGENTS D’ÉCHANGE CULTUREL: COMMENT LES NOUVEAUX ENSEIGNANTS D’ORIGINE AUTOCHTONE INFLUENCENT LE LANGUAGE ET LA CULTURE EN CLASSE RÉSUMÉ. Cet article fait le compte-rendu des révélations faites par six nouveaux enseignants d’origine autochtone au cours d’un cercle de discussion sur leur rôle d’enseignant. Les participants ont reproché aux programmes de formation des maîtres de ne pas les préparer à enseigner de manière respectueuse du langage et de la culture autochtones. Par ailleurs, ils ont souligné l’importance d’apprendre à se connaître et à explorer leur culture. En conclusion, les auteurs suggèrent des approches pour décoloniser la préparation des enseignants d’origine autochtone afin de leur permettre d’agir comme protecteurs de la culture autochtone et agents d’échange culturel avec la culture euro-canadienne. <!--EndFragment-->